2016
DOI: 10.1002/pola.28431
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining aliphatic branched polycarbonates via simple copolymerization of trimethylene carbonate with cyclic carbonate containing pendant ester groups

Abstract: Different possibilities for obtaining branched, functional carbonate copolymers are presented in this study. Copolymers were synthesized according to the ring‐opening polymerization (ROP) of the cyclic carbonate monomers, containing pendant ester groups. As an example, we chose copolymerization of ethyl 5‐methyl‐2‐oxo‐1,3‐dioxane‐5‐carboxylate (MTC‐Et) with trimethylene carbonate (TMC), using zinc (II) and lanthanum (III) acetylacetonates as ROP initiators. The transesterification processes of ester groups in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The same conclusions were noted in the case of our previous study relating to the copolymerization of TMC with MTC‐Et …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The same conclusions were noted in the case of our previous study relating to the copolymerization of TMC with MTC‐Et …”
Section: Resultssupporting
confidence: 87%
“…This was an expected effect since our previous studies showed low susceptibility of the carbonate groups to the transesterification reactions. Mechanism of this type of reaction has already been presented in detail in our previous article describing a model copolymerization of TMC with MTC‐Et . It occurs as a result of the attack of the active end of the growing chain onto the ester group located in the other molecule's side chain.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, an analogous phenomenon was already observed during the copolymerization of ethyl 5-methyl-2-oxo-1,3-dioxane-5-carboxylate (MTC-Et) with trimethylene carbonate (TMC) initiated with Zn[(acac) 2 H 2 O]. This process was much more intensive than that described in this work, as evidenced by the final dispersion of the molecular mass reaching a Ð value of more than 100 [21]. The growth of the amount of carbonate units in the obtained copolymers caused a decrease in their glass transition (T g ); however, this decrease was significantly slower than expected based on the calculation using the Fox equation (Table 1).…”
Section: Copolymerization Of L-lactide With 5-methyl-2-oxo-13-dioxane-5-carboxylate (Mtc-bz)supporting
confidence: 78%
“…Previously we described a very similar and analogical phenomenon, which proceeded during the polymerization of cyclic carbonates containing side ester groups [22]. A mechanism of transesterification in which the attack of active ends is directed to the ester bonds of the main chain is also very probable.…”
Section: Synthesis and Characterization Of L-lactide Copolymers With mentioning
confidence: 76%